Hubungan Masa Kerja, Jenis Kelamin dan Sikap Kerja dengan Keluhan Muskuloskeletal pada Operator SPBU di Kota Kupang - Kasimirus Ebu To; Noorce Ch. Berek; Agus Setyobudi (Media Kesehatan Masyarakat, 2020)
Musculoskeletal disorder (MSDs) is a disorder in workers. This work-related disease has a high prevalence globally. MSDs occurs in work environment that exposes workers to non-ergonomic posture. The disorder triggers fatigue and indirectly adds to the workload among workers. This study aims to analyze the relationship between work tenure, sex and work attitudes with musculoskeletal complaints in general refueling station operators in Kupang City. The research was an analytical survey with a cross-sectional design. The research were conducted at 15 General Refueling Stations in Kupang from October to November 2019. A sample of 69 people were selected from the population of 222 operators. Data were analyzed by using chi-square (X2) with p-value = 0,05. The results showed that there was a relationship between musculoskeletal complaints and length of work (ρ-value= 0,004), gender (ρ-value 0,007) and work attitude (ρ-value= 0,001).